The Rates and the Determinants of Hypertension According to the 2017 Definition of Hypertension by ACC/AHA and 2014 Evidence-Based Guidelines Among Population Aged ≥40 Years Old - Wenzhen Li; Dajie Chen; Shuai Liu; Xiaojun Wang; Xiaojie Chen; Jiafeng Chen; Jing Ma; Fujian Song; Hui Li; Shijiao Yan; Xiaoxv Yin; Shiyi Cao; et al. (Ubiquity Press, 2021)
Background: In November 2017, the American College of Cardiology/American Heart Association (ACC/AHA) updated their definition of hypertension from 140/90 mm Hg to 130/80 mm Hg. Objectives: We sought to assess the situation of hypertension and the impact of applying the new threshold to a geographically and ethnically diverse population. Methods: We analyzed selected data on 237,142 participants aged ≥40 who had blood pressure taken for the 2014 China National Stroke Screening and Prevention Project. Choropleth maps and logistic regression analyses were performed to estimate the prevalence, geographical distribution and risk factors of hypertension using both 2017 ACC/AHA guidelines and 2014 evidence-based guidelines. Results: The present cross-sectional study showed the age- and sex-standardized prevalence of hypertension was 37.08% and 58.52%, respectively, according to 2014 evidence-based guidelines and 2017 ACC/AHA guidelines. The distribution of hypertension and risk factors changed little between guidelines, with data showing a high prevalence of hypertension around Bohai Gulf and in south central coastal areas using either definition. The age- and sex-standardized prevalence of newly labeled as hypertensive was 21.44%. Interestingly, the high prevalence region of newly labeled as hypertensive was found in the north China. Conclusion: The prevalence of hypertension increased significantly on 2017 ACC/AHA guidelines compared to the prevalence when using 2014 evidence-based guidelines, with high prevalence areas of newly labeled as hypertensive now seen mainly in north China. There need to be correspondingly robust efforts to improve health education, health management, and behavioral and lifestyle interventions in the north.